Algebraic and categorical properties of r-ideal systems - Aleka Kalapodi; Angeliki Kontolatou (International Journal of Mathematics and Mathematical Sciences)
The structures (G,r), where r is a system of ideals defined on a directed group G, play an important role in solving arithmetical problems. In this paper, we investigate how some properties of these systems are transferred in their cartesian products and their substructures. The results we obtain find an application in the study of categorical properties of these structures.